Pencegahan Fraud Dalam Pelaporan Keuangan: Pendekatan Faktor Individu - Renya Rosari; Jems Zacharias; Mefibosed Radjah Pono (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
This study aims to find empirical evidence of the effect of morality, integrity and religiosity on fraud prevention in regional financial management. This research is an explanatory research, the approach used in this research is survey method. The population of this study were all employees at BPKAD Kota and Kabupaten Kupang. The sample in this study were 46 respondents of BPKD employees in the accounting and reporting divisions and regional assets. The data analysis technique used PLS Regression (Partial Last Square) path analysis using SmartPLS 3.0 software. This test is carried out in 3 stages, namely evaluating the outer model, 2) inner model, and  3) Hypothesis testing. The results of the study show that morality has an effect on fraud prevention, religiosity and integrity have no effect on fraud prevention in regional financial management.